Нормування та стандартизація термінології довідкових видань - Лісіна, Світлана (Видавництво Львівської політехніки, 2014)
The term creation features in reference publications are considered. The factors of their determination and mechanisms influencing the development of terminology are analyzed.
Keywords: термінологія; довідкове видання; енциклопедія; стандартизація